Replacing animal models : a practical guide to creating and using culture-based biomimetic alternatives - Davies, Jamie A. (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley - Blackwell, 2012)
"The book is neither political nor polemical: it is technical, illustrating by example how alternatives can be developed and used and providing useful advice on developing others. After looking at the reasons for and potential benefits of alternatives to animal experiments, the book covers a range of methods and examples emphasising the design considerations that went into each system. The chapters also include 'case studies' that illustrate the ways in which culture models can be used to answer a range of important biological questions of direct relevance to human development, physiology, disease and healing."--
Potential advantages of using biomimetic alternatives / Jamie Davies -- Overview of biomimetic alternatives / Jamie Davies -- Pancreatic islands / Eli C. Lewis -- Endometrial organoid culture / Merja Blauer -- Modelling lymphatic and blood capillary patterning / Francoise Bruyere [and others] -- Precision-cut lung slices (PCLS) / Christian Martin and Stefan Uhlig -- Human colon tissue in organ culture / Michael K. Dame and James Varani -- Fetal organs culture / Jamie Davies -- Design of a mechanical loading device to culture intact bovine spinal motion segments under multiaxial motion / Jochen Walser, Stephen John Ferguson, and Benjamin Gantenbein-Ritter -- Magnetic assembly of tissue surrogates / Chien-Yu Fu and Hwan-You Chang -- Assembly of renal tissues by cellular self-organization / Mathieu Unbekandt -- Hierarchical screening of pathways: using cell and organ cultures to reduce use of transgenic mice / Guangping Tai and Jamie Davies -- Lung organoid culture to study response to viruses / Wenxin Wu, J. Leland Booth, and Jordan P. Metcalf -- Organ-cultured human skin for the study of epithelial cell invasion of stroma / James Varani -- Organotypic mandibular cultures for the study of inflammatory bone pathology / Alastair J. Sloan, Sarah Y. Taylor, and Emma L. Smith -- Three-dimensional, high-density and tissue engineered culture models of articular cartilage / Ali Mobasheri [and others] -- Concluding remarks / Jamie Davies.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Alternative toxicity testing; Animal Testing Alternatives; Biomimetics -- methods; Models, Animal; SCIENCE -- Life Sciences -- Molecular Biology; Alternative toxicity testing; Electronic books; Electronic books